Social capital versus social theory : political economy and social science at the turn of the millennium - Fine, Ben (Contemporary political economy series., 2001)
This volume traces the origins of social capital through the work of Becker, Bourdieu and Coleman, and comprehensively reviews the literature across the social sciences.